(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2020)
This paper deals with the interpretation of Sophocles’ Antigone as developed by Jacques Lacan in the Book VII of the Seminar. In contrast with traditional ethical analyses from Aristotle to Kant, the author emphasizes the absolute and radical desire of Antigone, whose fulfillment leads to the ultimate limit of life. In spite of her extreme rigidity, Antigone represents the possibility of assuming ethically one’s own desire, accepting its paradoxical dimension. Therefore, the psychoanalytic interpretation of the tragedy Antigone leads to accept desire’s destabilizing force. From this point of view, the practice of analysis finds an effective contribution in the experience of tragedy: in this sense, it is possible to highlight the relationship between an action and the desire that inhabits it. Through the contrasting readings given by Slavoj Žižek and Massimo Recalcati, this paper is aimed to show how the ethical dimension of Sophocles’ Antigone does not match with the ideals of traditional ethics, but allows us to explore the limit of human desire.